1996
DOI: 10.1073/pnas.93.20.10933
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline-mediated quantitative and tissue-specific control of gene expression in transgenic mice.

Abstract: The tet regulatory system in which doxycycline (dox) acts as an inducer of specifically engineered RNA polymerase II promoters was transferred into transgenic mice. Tight control and a broad range of regulation spanning up to five orders of magnitude were monitored dependent on the dox concentration in the water supply of the animals. Administration of dox rapidly induces the synthesis of the indicator enzyme luciferase whose activity rises over several orders of magnitude within the first 4 h in some organs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
556
2
8

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 722 publications
(580 citation statements)
references
References 23 publications
13
556
2
8
Order By: Relevance
“…[14][15][16] However, proper synthesis and membrane insertion of the receptor in other tissues, tissue-specific retention of FESP metabolites in non-D 2 R-dependent fashion, and other variables may modify imaging of the D 2 R reporter gene product. To determine carefully lower levels of detection of this reporter gene in vivo, D 2 R reporter gene expression in inducible models [36][37][38] will need to be characterized. It is clear, however, that we can quantitatively determine expression of the D 2 R reporter gene with FESP in vivo, both when the D 2 R is expressed from an infecting viral vector and when the D 2 R is expressed from a stably integrated foreign promoter in heterologous tissue.…”
Section: U Of Ad-d 2 R Virus Two Days Later Mouse B Was Injected Imentioning
confidence: 99%
“…[14][15][16] However, proper synthesis and membrane insertion of the receptor in other tissues, tissue-specific retention of FESP metabolites in non-D 2 R-dependent fashion, and other variables may modify imaging of the D 2 R reporter gene product. To determine carefully lower levels of detection of this reporter gene in vivo, D 2 R reporter gene expression in inducible models [36][37][38] will need to be characterized. It is clear, however, that we can quantitatively determine expression of the D 2 R reporter gene with FESP in vivo, both when the D 2 R is expressed from an infecting viral vector and when the D 2 R is expressed from a stably integrated foreign promoter in heterologous tissue.…”
Section: U Of Ad-d 2 R Virus Two Days Later Mouse B Was Injected Imentioning
confidence: 99%
“…Therefore, we developed an inducible tumor cell line in which wild-type p53 gene expression is controlled by a tetracycline-dependent promoter. 13,14 Using this model, we recently showed that induction of wt-p53 increases the expression of the pro-apoptotic BAX protein in its native, inactive conformation without triggering apoptosis. 14 Thus, we used this model to analyze whether or not the antitumoral activity of wt p53 is dependent on its pro-apoptotic function.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that a supply of tet in drinking water leads to a continuous dissemination of the antibiotic in different tissues, whereby tet is readily absorbed and broadly distributed without toxicity at the concentration needed to regulate the activity of the promoter. 10 This was demonstrated for vascularized tissues such as the liver in transgenic mice. 10 We have proven that the antibiotic also easily accesses nonvascularized tissue, such as a depot of tumor cells in a s.c. pocket.…”
Section: Discussionmentioning
confidence: 91%
“…10 This was demonstrated for vascularized tissues such as the liver in transgenic mice. 10 We have proven that the antibiotic also easily accesses nonvascularized tissue, such as a depot of tumor cells in a s.c. pocket. This assumption derives from the observation that the effect of inhibiting IL-2 expression was readily visible already at the start of tumor growth (i.e., at 10 days after application of the tumor cells and tet, respectively).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation